"Evaluation of a method to measure the friction coefficient between vital mandibular bone and biomedical materials". (December 2021) - Ben Achour, Anas; Petto, Carola; Meißner, Heike; Mostofa, Anita; Teicher, Uwe; Ihlenfeldt, Steffen; Lauer, Günter
Abstract: Purpose: The aim of this study is to evaluate a developed experimental set-up to measure the coefficient of friction between fresh mandibular bone and biomaterials used in oral and maxillofacial surgery including a standardized routine for specimen preparation. Material and methods: For this purpose, we developed a specialized routine for harvesting and preparation of cortical bone specimen from cadaveric porcine mandibles and modified a ball-plate tribometer. These harvested bone specimen were kept moist all the time. A total of 24 bone cylinders with 8 repetitions per material were examined for their coefficient of friction against stainless steel (1.4404), a titanium alloy (Ti6Al4V) and a cobalt‑chromium‑molybdenum alloy (Biosil F®) and subsequently analyzed by laser-scanning and scanning electron microscopy. Results: The lowest coefficients of friction between vital cortical bone and the investigated implant materials were found for Biosil F®, while the highest coefficients of friction were found for the titanium alloy Ti6Al4V. Significant differences for the initial coefficient of friction with p  < 0.05 have been proven. Stick-slip effects occurred during the measurement and a layer of debris formed on the metallic samples. EDX analysis of the abrasion marks revealed that this layer consisted of elements contained in hydroxyapatites and carbon. Conclusion: The experimental set-up is suitable to perform reproducible comparative measurements of the coefficient of friction of different material combinations. A significant advantage of the methodology is the flexibility and scalability of harvesting and preparation of the bone specimen, which allows the simulation of realistic situations while measuring the coefficient of friction. Highlights: Standardized specimen preparation is necessary for the comparability of results when determining the coefficient of friction Friction coefficients are influenced by the implant material Wear of bone material and no wear of the metallic specimens takes place in tribological examinations